Fracture properties of GGBFS-blended fly ash geopolymer concrete cured in ambient temperature - Nath, P.; Sarker, Prabir (Springer Netherlands, 2016)
Fracture characteristics are important part of concrete design against brittle failure. Recently, fly ash geopolymer binder is gaining significant interest as a greener alternative to traditional ordinary Portland cement (OPC). Hence it is important to understand the failure behaviour of fly ash based geopolymers for safe design of structures built with such materials. This paper presents the fracture properties of ambient-cured geopolymer concrete (GPC). Notched beam specimens of GPC mixtures based mainly on fly ash and a small percentage of ground granulated blast furnace slag were subjected to three-point bending test to evaluate fracture behaviour. The effect of mixture proportions on the fracture properties were compared with control as well as OPC concrete. The results show that fracture properties are influenced by the mixture compositions. Presence of additional water affected fracture properties adversely. Fracture energy is generally governed by tensile strength which correlates with compressive strength. Critical stress intensity factor varies with the variation of flexural strength. Geopolymer concrete specimens showed similar load–deflection behaviour as OPC concrete specimens. The ambient cured GPC showed relatively more ductility than the previously reported heat cured GPC, which is comparable to the OPC specimens. Fly ash based GPC achieved relatively higher fracture energy and similar values of KIC as compared to those of OPC concrete of similar compressive strength. Thus, fly ash based GPC designed for curing in ambient condition can achieve fracture properties comparable to those of normal OPC concrete.